(untitled) (GYMNASIUM, 2020)
Nowadays, the level of professional volleyball has increased significantly, having such dynamic and speed of execution of the game actions, that it is very difficult to watch the game in its depth without using some special programmes of statistical analysis. In this context, for a fair and precise assessment of the game actions, there are used both statistical, as well as video evaluation software programmes, so as not to miss any important detail during the games. One of the most used programmes in professional volleyball is “Data Volley”, which includes a video system of analysis and evaluation called “Data Video”. These were designed so as to simplify the work of the coaches, in analysing their own game, as well as that of the other team. The purpose of this study is to analyse the game of the other team before official games, on offence and defence, using the “Data Video” system.